Death revisited The excavation of three Bronze Age barrows and surrounding landscape at Apeldoorn-Wieselseweg - Louwen, Arjan; Fontijn, David (Sidestone Press, 2019)
This book has been a long time in the making. When we left the field for the final time in 2009 we could only guess at what exactly we had found - we did not even have firm dates for most of the graves discovered. The post-excavation analysis of the finds and features proved to be a challenging task, and our interpretations had to be adjusted several times. This was for an important part due to the very complex soils and difficult-to-read features that made even the simplest questions such as 'where does a mound begin and end' difficult to answer.